In vitro and in vivo protection against the highly pathogenic H5N1 influenza virus by an antisense phosphorothioate oligonucleotide - Duan, Ming; Zhou, Zhe; Lin, Ru-Xian; Yang, Jing; Xia, Xian-Zhu; Wang, Sheng-Qi (Antiviral therapy, 2008)
Current vaccination strategies and antiviral drugs only provide limited protection against influenza virus infection. In this study, we investigated the use of a novel antisense oligonucleotide (named IV-AS), which is specific for the 5'-terminal conserved sequence found in all eight viral RNA segments of influenza A virus. The activity of IV-AS was monitored both in vitro, in Madin-Darby canine kidney (MDCK) cells, and in vivo using a mouse model. IV-AS was given intranasally to H5N1-infected mice once daily for 6 days starting 6 h after infection. A three-base mismatch of IV-AS was used as a control. IV-AS inhibited influenza virus A induced cytopathic effects in MDCK cells with the 50% effective concentration (EC50) ranging from 2.2 to 4.4 microM. IV-AS was effective against H5N1 virus in preventing death, lessening weight reduction, inhibiting lung consolidation and reducing lung virus titres. Dosages of 40 and 60 mg/kg/day provided 40% and 60% survival rates and prolonged mean survival days in comparison with the infected control group (P<0.05). The lung index in mice treated with IV-AS, at a dose of 20, 40 or 60 mg/kg/day, had been inhibited on day 4 or 6 (P<0.05 or P<0.01); virus titres in lung had declined to 2.42, 1.51 and 1.54 log10 TCID50/g of lung, respectively, whereas the yields in the infected control mice were 6.00 log10 TCID50/g of lung. Our results suggest that the 5'-terminal conserved region of influenza A virus RNA segments can be targeted using antisense technology; therefore, IV-AS is a potential drug for prophylaxis and control of influenza virus infections.